2009
DOI: 10.1111/j.1365-313x.2009.03968.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP is a regulator of pathogen defence in plants

Abstract: SUMMARYIn healthy plants extracellular ATP (eATP) regulates the balance between cell viability and death. Here we show an unexpected critical regulatory role of eATP in disease resistance and defensive signalling. In tobacco, enzymatic depletion of eATP or competition with non-hydrolysable ATP analogues induced pathogenesisrelated (PR) gene expression and enhanced resistance to tobacco mosaic virus and Pseudomonas syringae pv. tabaci. Artificially increasing eATP concentrations triggered a drop in levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 99 publications
(211 reference statements)
1
114
0
4
Order By: Relevance
“…Extracellular purine nucleotides have been shown to be involved in the regulation of plant cell viability, membrane permeability, immunity, symbiosis, stress responses, and growth (Lew and Dearnaley, 2000;Tang et al, 2003;Chivasa et al, 2005Chivasa et al, , 2009Kim et al, 2006Kim et al, , 2009Roux and Steinebrunner, 2007;Wu et al, 2007;Riewe et al, 2008a;Wu and Wu, 2008;Yi et al, 2008;Demidchik et al, 2009;Govindarajulu et al, 2009;Kim et al, 2009;Clark et al, 2010aClark et al, , 2010bTanaka et al, 2010aTanaka et al, , 2010bTerrile et al, 2010;Tonó n et al, 2010). Purine nucleotide release from plant cells may occur through wounding, exocytosis, or through the activity of plasma membrane (PM) ATP-binding cassette transporters (Thomas et al, 2000;Kim et al, 2006).…”
mentioning
confidence: 99%
“…Extracellular purine nucleotides have been shown to be involved in the regulation of plant cell viability, membrane permeability, immunity, symbiosis, stress responses, and growth (Lew and Dearnaley, 2000;Tang et al, 2003;Chivasa et al, 2005Chivasa et al, , 2009Kim et al, 2006Kim et al, , 2009Roux and Steinebrunner, 2007;Wu et al, 2007;Riewe et al, 2008a;Wu and Wu, 2008;Yi et al, 2008;Demidchik et al, 2009;Govindarajulu et al, 2009;Kim et al, 2009;Clark et al, 2010aClark et al, , 2010bTanaka et al, 2010aTanaka et al, , 2010bTerrile et al, 2010;Tonó n et al, 2010). Purine nucleotide release from plant cells may occur through wounding, exocytosis, or through the activity of plasma membrane (PM) ATP-binding cassette transporters (Thomas et al, 2000;Kim et al, 2006).…”
mentioning
confidence: 99%
“…In addition, when an increase in the eATP concentrations compromised the resistance of tobacco leaves to viral and bacterial infection, the SA content was obviously decreased ). Furthermore, Chivasa et al (2009) found that the treatment of tobacco leaves with SA decreased the level of eATP, which preceded the induction of PR by SA, and blocking of this reduction in the eATP level suppressed the SA-induced expression of PR genes. These observations imply that the eATP-mediated plant defence responses may be associated with SA, and the ability of SA to induce defence responses could also be associated with eATP.…”
Section: Plant Defence Responses To Pathogens and Eatpmentioning
confidence: 94%
“…Song et al (2006) reported that in arabidopsis leaves the genes encoding the enzymes for JA and ET (ethylene) biosynthesis were induced by exogenous ATP, implying that eATP could also have the ability to increase the content of JA and ET (although this has not been confirmed by any scientific reports). Chivasa et al (2009) revealed that treatment with exogenous ATP caused a decrease of SA content of tobacco leaves.…”
Section: Signalling Molecules Involved In Plant Defence Responses Arementioning
confidence: 97%
“…Slabas and colleagues reported that the removal of eATP caused expression of pathogenesis-related (PR) genes and cell death. [29][30][31] It has shown that the plant response to eATP is dosedependent. In Arabidopsis, low concentrations of eATP (15-35 mM) triggered the opening of stomata while high concentrations (greater than 250 mM) caused stomatal closure.…”
Section: Eatp-mediated Cellular Events In Plantsmentioning
confidence: 99%
“…In tobacco leaves, enzymatic depletion of eATP triggered salicylic acid (SA)-dependent PR gene expression and enhanced resistance to tobacco mosaic virus and Pseudomonas syringae pv tabaci. 30 Artificially addition of ATP reversed the effects of eATP depletion on gene expression and pathogen resistance. 30 The above mentioned results show that the eATP degradation during pathogen infecting is an important signaling to induce downstream defense responses and hypersensitive cell death.…”
Section: Disruption Of Eatp Homeostasis Initiates Cell Death In Plantsmentioning
confidence: 99%